2017
DOI: 10.1017/s0885715617001129
|View full text |Cite
|
Sign up to set email alerts
|

X-ray powder diffraction data and characterization of Mirabegron

Abstract: Mirabegron, (C21H24N4O2S), is a β3-adrenoceptor agonist approved in Japan, the USA, Canada and Europe, for the treatment of overactive bladder symptoms. There are no entries for this important active pharmaceutical ingredient in the Cambridge Structural Database or the Powder Diffraction File-4/Organics database. In this contribution, the powder diffraction pattern of Mirabegron, an unreported phase, are presented with a study by spectroscopy methods (Fourier-transform infrared spectroscopy [FT-IR] and RAMAN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The simulated powder X‐ray diffraction (PXRD) spectrum matched well with the previously reported PXRD data (Figure S2 in Supporting Information). [ 9 ] The consistent spectra indicate that the MicroED structure reflects for the entire powder, rather than a rare portion. Within the MicroED structure, conformer 1 and conformer 2 form tightly stacked pairs through eight hydrogen bonds, creating a dense three‐dimensional network ( Figure ; Table S3 in Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The simulated powder X‐ray diffraction (PXRD) spectrum matched well with the previously reported PXRD data (Figure S2 in Supporting Information). [ 9 ] The consistent spectra indicate that the MicroED structure reflects for the entire powder, rather than a rare portion. Within the MicroED structure, conformer 1 and conformer 2 form tightly stacked pairs through eight hydrogen bonds, creating a dense three‐dimensional network ( Figure ; Table S3 in Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…Mendoza et al reported the PXRD spectrum of Mirabegron, identifying it as a triclinic space group P1 (a = 5.35Å, b = 11.61Å, c = 17.59Å, 𝛼 = 70.79°, 𝛽 = 84.42°, 𝛾 = 86.29°). [9] Tamayo et al later reported PXRD and DFT refinement for Mirabegron, but without an available structure. [10] In a single particle Cryo-EM study of Mirabegron bound to dog 𝛽3AR, Mirabegron adopted a conformation that was different than the expected conformation based on the synthesis alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline nature of the sample is determined by X-ray diffraction [43]. One can easily differentiate between crystalline and amorphous forms based on the peak intensities and positions by X-ray powder diffraction [44]. Diffraction patterns of powder mirabegron were recorded on BRUKER D8 ADVANCE diffractometer by [44].…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 99%
“…It is available in the market since 2013 [8]. Mirabegron is an official drug indicated for OAB in Japan, USA, Canada, and Europe [9]. Mirabegron is used with or without combination with anti-cholinergic drugs such as solifenacin succinate, darifenacin, and fesoterodine to treat urinary incontinence [10].…”
Section: Introductionmentioning
confidence: 99%